The performance management system for educational staff at Motheo College: an evaluative case study - Venter, Helouise (University of the Free State, 2006)
Worldwide, including in South Africa, Performance Management (PM) has become paramount within knowledge-producing institutions – not only to survive the extremely competitive and interconnected world we live in, but also to meet the demands for quality, accountability and high-level people power. Performance Management, embedded in human resource management and development (HRMD), has become critical in guiding and supporting the strategic (re-) planning of such institutions. The PM Project (of which this study forms part, with special reference to Motheo Further Education and Training (FET) College cluster) of the Centre for Higher Education Studies and Development (CHESD) at the University of the Free State was initiated with the purpose of addressing the shortcomings of current PM processes within South African further and higher education institutions. This is particularly significant since PM practices is a relatively recent phenomenon in further and higher education and also because HRMD in South Africa is an underdeveloped and poorly resourced function. In order to address the above-mentioned complex challenges, the aim of this study was to develop an effective and efficient performance management system (PMS) for the Motheo FET College cluster by: • undertaking a comprehensive literature and policy review on PM in the higher and further education and training sectors; and • investigating and critically analysing the existing PMS at the Motheo FET College cluster. Findings of the above-mentioned formative evaluative case study approach were based on qualitative (i.e. eleven semi-structured interviews with educators) and quantitative (i.e. a questionnaire survey targeting 157 educators) investigations. The main findings and conclusions from these investigations indicated an urgent need to formally implement an effective and efficient PMS at this institution for human and social development as well as for transformation purposes (where team-building amongst campuses and preparation of staff will be required). In addition, a structured PMS could then guide these educators by ensuring that they are able to keep abreast of developments in their own fields of teaching, as well as of changes in environment, teaching methods and technologies (especially since the merger, and because of multiple legislative demands). From the literature it has become evident that PM is normally a complicated and delicate matter. In this study the lack of communication between educators and management in terms of performance-related information was identified. In the light of this it is crucial to inject additional resources into management development (alongside the existing staff development and training), in order to prepare members of management to cope with change. It is also essential for educators to increase and enhance their performance and to prevent the loss of quality educators to other institutions. The perspectives and insights gained from the evaluative case study could guide the managers of the Motheo FET College cluster to develop an effective and efficient PMS, and indirectly to improve the educators’ knowledge and skills in becoming and remaining professionals in their respective fields.

Tans is prestasiebestuur wêreldwyd en in Suid Afrika van groot waarde, by alle leerinstellings, ter wille van oorlewing in ‘n kompetisie-gedrewe wêreld. Instellings bly steeds aanspreeklik teenoor kliente vir die lewering van kwaliteit dienste en die opleiding van menslike hulpbronne. Dus, gewortel in menslike hulpbronbestuur en -ontwikkeling, het prestasiebestuurstelsels ‘n kritiese padwyser geword in die strategiese herbeplanning in die leerinstellings. Aansluitend by die bogenoemde is ‘n prestasiebestuur projek onderneem deur die Sentrum vir Hoëronderwys Studie en Ontwikkeling verbonde aan die Universiteit van die Vrystaat. As deel van die projek verwys hierdie studie spesifiek na die Motheo Verdere Onderwys en Opleiding (VOO) Kollege. Die doel van die oorkoepelende projek was om die tekortkominge in die huidige prestasiebestuurstelsels in Suid-Arikaanse hoër en verdere onderwys uit te wys. Daar word allerweë erken dat prestasiebestuurpraktyke ‘n nuwe tendens in hoër en verdere onderwys is, en dit is ook ‘n feit dat menslike hulpbronbestuur en -ontwikkeling in Suid-Afrika ook ‘n geskiedenis het van onderontwikkeling. Met die oog op bogenoemde uitdagings was die doelwit van die studie die ontwikkeling en daarstelling van ‘n effektiewe en bruikbare prestasiebestuurstelsel by Motheo VOO Kollege deur: • ‘n uitgebreide literatuur en beleidstudie oor prestasiebestuur in hoёr en verdere onderwys sektore te onderneem, en • om navorsing en ‘n kritiese analiserig van die huidige prestasiebestuurstelsel by Motheo VOO kollege te doen. Bevindinge van hierdie formatiewe gevallestudie is gebaseer op ‘n ondersoek met ‘n kwalitatiewe benadering (elf onderhoude met dosente) en ‘n kwantitatiewe benadering (‘n vraelys wat aan 157 dosente uitgedeel is). Navorsing het bewys dat daar ‘n dringende behoefte is aan die implementering van ‘n prestasiebestuurstelsel vir menslike, sosiale en ook transformasie doeleindes (met spanbou en samewerking tussen die drie kampusse ingesluit). Vervolgens kan ‘n prestasiebestuurstelsel onderigpersoneel bystaan om aan te pas by ‘n veranderende omgewing op vakgebiede, tegnologie en onderigmetodes (veral sedert die samesmelting van die kolleges en as gevolg van nuwe wetgewing). Die komplekse delikaatheid van ‘n prestasiebestuurstelsel het duidelik uit die literatuur na vore gekom. Die studie het ook die gebrek aan kommunikasie, veral oor prestasiebestuur, tussen bestuur en onderrigpersoneel uitgewys. In die lig hiervan is dit belangrik dat addisionele hulpbronne vir die opleiding en ontwikkeling van bestuurslede verleen word om te verseker dat hulle die personeel kan bystaan en effektief kan bestuur in ’n veranderde omgewing. Vervolgens kan dosente hul prestasies verbeter en sodoende verhoed dat bekwame personeel verlore raak omdat ander sektore vir hulle beter opsies bied. Die gevolgtrekkings en bevindinge kan dit moontlik maak vir die bestuur van Motheo VOO kollege om ondermeer ŉ effektiewe en bruikbare prestasiebestuurstelsel te ontwikkel en te implementeer sodoende ook dosente se kennis en vaardighede te verbeter om professioneel te wees in hulle velde.
Dissertation (M.A. (Higher and Further Education))--University of the Free State, 2006
Keywords: Universities and colleges -- South Africa -- Bloemfontein; College teachers -- Rating of -- South Africa -- Bloemfontein